2003
DOI: 10.1186/1471-2253-3-2
|View full text |Cite
|
Sign up to set email alerts
|

Risk of whole body radiation exposure and protective measures in fluoroscopically guided interventional techniques: a prospective evaluation

Abstract: Background: Fluoroscopic guidance is frequently utilized in interventional pain management. The major purpose of fluoroscopy is correct needle placement to ensure target specificity and accurate delivery of the injectate. Radiation exposure may be associated with risks to physician, patient and personnel. While there have been many studies evaluating the risk of radiation exposure and techniques to reduce this risk in the upper part of the body, the literature is scant in evaluating the risk of radiation expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(40 citation statements)
references
References 25 publications
3
37
0
Order By: Relevance
“…Thus, if the distance doubles, the radiation exposure level drops 4 times [3]. In general, the scattered radiation level from the patients when standing 1 m apart is only about 0.1% of the patient's absorbed dose rate [6]. In Figs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, if the distance doubles, the radiation exposure level drops 4 times [3]. In general, the scattered radiation level from the patients when standing 1 m apart is only about 0.1% of the patient's absorbed dose rate [6]. In Figs.…”
Section: Resultsmentioning
confidence: 99%
“…The three different measurements of the dosimeters were all within the permissible range. Other studies have shown the radiation measurements for fluoroscopy-guided intervention pain procedures to be within the permissible range [6][7][8][9][10][11][12], but the natural radiation exposure dose in daily life is 2.4 mSv.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the first randomized study patients were split into 2 groups with endoscopy without adhesiolysis and with adhesiolysis. Patients with adhesiolysis showed a significant pain relief (>50%) in follow‐up for at least 6 months [1]. The second randomized study compared caudal steroid injections with steroid placement during epiduroscopy and showed no significant reduction of pain in the epiduroscopy group compared with the other group [2].…”
mentioning
confidence: 99%